Thermal decomposition of some analgesic agents - Ribeiro, Y. A. [UNESP]; De Oliveira, J. D S [UNESP]; Leles, M. I G [UNESP]; Juiz, S. A. [UNESP]; Ionashiro, Massao [UNESP] (Springer Nature, 1996)
Thermogravimetry, derivative thermogravimetry (TG, DTG) and differential scanning calorimetry (DSC), were used to study the thermal behaviour of mefenamic acid, ibuprofen, acetaminophen, sodium diclofenac, phenylbutazone, dipyrone and salicylamide. The results led to thermal stability data and also to the interpretation concerning the thermal decomposition. © 1996 Akadémial Kiadó.
Keywords: Acetaminophen; Dipyrone; Ibuprofen; Mefenamic acid; Phenylbutazone; Salicylamide; Sodium diclofenac; Thermal decomposition; Differential scanning calorimetry; Differential thermal analysis; Pyrolysis; Thermodynamic stability; Thermogravimetric analysis; Analgesics; Derivative thermogravimetry; Drug products